Development of a single-step SYBR Green based Real-Time PCR assay for identification and quantification of Fowlpox virus in Chicken - Sanganagouda , K; Kounin, Sabha; Nagraja , K; Sajjanar, Basavaraj; Gomes, Amitha Rena; Sahoo, Aditya Prasad; Alamelu , M S (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Fowlpox is a re-emerging and economically significant viral disease in poultry. Fowlpox is a complex virus contains a double-strand DNA genome of approximately 300 kb and largest among all poxviruses. In the present study, a clinical case of fowlpox virus [FPV] infection was investigated and a Real-Time PCR assay was developed for confirmatory diagnosis of Fowlpox and quantification of viral load.  Clinical sample was collected from infected bird reared in the organized poultry farm management system and the viral infection  was  confirmed using conventional PCR amplification of the P4b gene of FPV. Following that, a Single-step SYBR Green based Real-Time PCR assay was developed by targeting the same gene of FPV. The Fowlpox viral load in the infected bird was found to be 7.33 ± 0.044 [Log Mean ± SD]. The lower detection limit achieved was 134 copies/ μl with a corresponding threshold cycle [Ct] value of 32.59. Thus, the single-step SYBR Green based Real-Time PCR assay targeting the P4b gene of FPV reported in this study was highly sensitive, specific and reproducible for the detection and quantitation of FPV nucleic acids.
Keywords: P4b gene; Fowl pox; Real-Time PCR; SYBR green; Viral load